Comparative assessment of infiltration, runoff and erosion sprinkler irrigated soils - Santos, Francisco Lúcio (2012)
Abstract The impacts of sprinkler irrigation on infiltration, runoff and sediment loss of ten representative soils of Southern Portugal were assessed by laboratory sprinkler irrigation simulation tests. All soils showed very low permeability to applied water. The mechanical impact of water droplets enhanced soil dispersion and further lowered their infiltration capacity, particularly for high clay plus silt content soils that showed the poorest results. As a consequence, high runoff and sediment losses were also measured, primarily with the first irrigation. More moderate losses were observed thereafter. Soils with higher sand particle size fractions better absorbed the energy impact of droplets and showed higher infiltration rates and lower runoff and sediment losses. Polyacrylamide (PAM) applied to the soils through the irrigation water acted as a binding and settling agent to increase soils aggregate stability and infiltration and reduce runoff and sediment losses. Slope increase, from 2·5 to 5%, decreased overall soils infiltration by 7% and increased runoff and sediment losses by 10 and 27%, respectively. Exposed to the same change in slope, PAM application boosted overall infiltration of treated soils to a 24% difference and increased runoff by only 10%. It had a less positive effect on sediment loss, the 5% slope being responsible for a 52% increase. In agreement with this the tests showed that, compared to the control, exposure of PAM-treated soil on 2·5 and 5% slopes enhanced overall infiltration to 457 and 642% respectively, reduced runoff by 25% on both cases and lessened sediment loss by 39 and 27%. The demonstrated ability of PAM to influence surface soil conditions of specific soils can be used to reduce the environmental risks associated with the intensive use of sprinkler irrigation in Southern Portugal. It offers a safe, practical and non-intrusive management alternative to current costly, labour- and energy-intensive practices of increasing the number of machine turns and building storage basins to control runoff and soil erosion.